TRAFFIC MANAGEMENT OF SIMPANG TUJUH ULEE KARENG INTERSECTION, BANDA ACEH - Fadhli (NIM : 250 04 062), Noer
Abstrak: An intersection consists of two or more roads. It is a place where vehicle traffic can change its direction. Simpang Tujuh Ulee Kareng intersection is a very complex intersection that consists of seven legs. The purpose of the research was to evaluate the performance of the Simpang Tujuh Ulee Kareng intersection. The evaluation was carried out for several conditions. The existing condition, Traffic signal simulation condition, intersection geometric improvement condition, and their combination were applied in the research. SIDRA Program and Method of MKJI were also used in the research. The result by SIDRA program shows that the performance of the intersection in the existing condition is very bad, where the Monday peak flow was 2271 pcph, the maximum capacity was 2799 pcph and the average delay was 448,9 seconds. The signal simulation by SIDRA resulted capacity of 3373 pcph, degree of saturation of 1.286 and average delay of 433.4 seconds. The results by SIDRA with unsignalized intersection geometric improvement and flow of 2143 pcph were the maximum capacity of 2212 pcph, the degree of saturation of 1,245 and the average delay of 183.3 seconds. The results by SIDRA with signalized intersection geometric improvement were the maximum capacity of 3278 pcph, the degree of saturation of 0.956 and the average delay of 39.1 seconds. The MKJI method with unsignalized intersection geometric improvement resulted and flow of 2212 pcph resulted a maximum capacity of 4039 pcph, degree of saturation of 0,55 and average delay of 10.10 seconds. The MKJI method with signalized intersection geometric improvement and flow of 1515 pcph resulted a maximum capacity of 2773 pcph, degree of saturation of 0,55 and average delay of 23.76 seconds.